Dietary intake of Vitamin D and its relation with blood pressure in the elderly population - Hossein Faraji; Sanaz Jamshidi; Sara Beigrezaei; Gholamreza Askari (International Journal of Preventive Medicine, 2019)
Background: Population studies have demonstrated that there is an inverse association between dietary intake of vitamin D and the mean blood pressure in elderly in particular. So, we investigated the correlation between vitamin D intake and the mean blood pressure in the elderly with and without nursing care. Methods: Based on a cross-sectional design, this study was conducted on 152 old people with and without nursing care. Assessment of the dietary intake of nutrients was done by an expert dietitian using food frequency questionnaire and nutritionist IV software analyzer. Also, the mean blood pressure was extracted from participants' files. The independent samplet-test, Chi-square test, and partial correlation test were used for data analysis. Results: Mean ± SD age, weight, height, body mass index (BMI) of participants, and the percentage of male/females were 68.7 ± 5.5 years, 63.5 ± 7.9 kg, 162.5 ± 7.1 cm, 24.1 ± 3.4 kg/m2 and 48.7/51.3, respectively. Also, a significant negative relationship was observed between vitamin D intake and systolic blood pressure in all participants (P value = 0.028, r = −0.179). There was no significant correlation between vitamin D intake and diastolic blood pressure (P value = 0.558, r = −0.048). Conclusions: The findings revealed that the nursing care can improve dietary intake of vitamin D in the elderly population. Also, a negative correlation was found between vitamin D intake and systolic blood pressure among all the elderly.